Influence of linker length in shape recognition of B∗ DNA by dimeric aminoglycosides. Issue 13 (1st July 2015) - Kumar, Sunil; Spano, Meredith Newby; Arya, Dev P.
Graphical abstract: Abstract: DNA-protein recognition has shown us the importance of DNA shapes in the recognition process. Specific high-affinity targeting of DNA shapes by small molecules is desirable for many biological applications that involve regulation of DNA based processes. Here, the effect of linker length and rigidity on the affinity of a conjugated neomycin dimer for a specific DNA shape (B ∗ form) AT-rich DNA was explored. Binding constants approximating 10 8  M −1 for optimal linker lengths of 18–19 atoms are reported herein.